Adolescents and Internet Sex Addiction - Dini Farhana Baharudin; Mohd Zaliridzal Zakaria (2024)
Very little thought or research has been directed to the topic of adolescents and sex addiction. Adolescents who use the Internet regularly present a new set of challenges for therapists. This article examines (a) the basic concepts and unique psychological characteristics of the Internet that relates to adolescents’ online sexual behaviors, (b) the etiology of adolescents’ Internet sex addiction, and (c) treatment and prevention when dealing with problematic online sexual behavior in adolescents. It is concluded that therapists cannot ignore the role that the media, particularly the Internet, plays in adolescents’ life and its impact on the family and society.